2016
DOI: 10.1007/s40299-016-0315-0
|View full text |Cite
|
Sign up to set email alerts
|

Struggling to Thrive: The Impact of Chinese Language Assessments on Social Mobility of Hong Kong Ethnic Minority Youth

Abstract: The paper explores how the policy of alternative Chinese qualifications policy affect ethnic minorities' (EM) social mobility, and how such multi-exit assessment framework affect Chinese as a second language (CSL) learning and teaching in Hong Kong. Chinese language (CL) qualifications other than the Hong Kong Diploma of Secondary Education have been accepted by the University Grants Committee (UGC)-funded institutions in Hong Kong as university admission requirements, including General Certificate of Secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Our review revealed to a greater extent examples of language perceived as a critical gap separating immigrant students from learning and from their teachers, and as a gap separating teachers from effectively teaching. This was evident in HK, where ethnic minorities’ lack of mastery of Chinese (Cantonese and Putonghua) or standard English detrimentally affects their school performance (Gu, 2018; Shum et al, 2018) and social mobility (Loh & Tam, 2016). Researchers in Turkey (Aydin & Kaya, 2017; Aykırı, 2017) documented teachers’ inability to communicate with refugee students or their parents because of language barriers, exacerbated further by the shortage of sufficiently trained teachers who can instruct immigrant students.…”
Section: Resultsmentioning
confidence: 99%
“…Our review revealed to a greater extent examples of language perceived as a critical gap separating immigrant students from learning and from their teachers, and as a gap separating teachers from effectively teaching. This was evident in HK, where ethnic minorities’ lack of mastery of Chinese (Cantonese and Putonghua) or standard English detrimentally affects their school performance (Gu, 2018; Shum et al, 2018) and social mobility (Loh & Tam, 2016). Researchers in Turkey (Aydin & Kaya, 2017; Aykırı, 2017) documented teachers’ inability to communicate with refugee students or their parents because of language barriers, exacerbated further by the shortage of sufficiently trained teachers who can instruct immigrant students.…”
Section: Resultsmentioning
confidence: 99%
“…Many underprivileged South Asians are limited to low-paid service jobs that require them to be proficient in the local vernacular to communicate with most working-class people in Hong Kong (Lai, 2010 ). As a minoritized group, they are expected to be assimilated into mainstream Chinese society by studying Chinese to achieve a social class upgrade (Loh & Tam, 2016 ). In contrast, their wealthier white counterparts have the privilege of thriving in Hong Kong as monolingual English speakers who receive elite English-medium education in fee-paying international schools where Cantonese-speaking is discouraged or even disallowed on campus.…”
Section: A Social Justice Perspective Of Language Educationmentioning
confidence: 99%
“…Their conclusion was that poor Chinese teaching was to blame (Wang, 2019 ). In the past decade or so, Chinese language education, its pedagogy, assessment methods, and teachers have been frequently criticized by researchers and the news media for the academic failures of Hong Kong’s ethnic minority students (Loh & Tam, 2016 ; Shum et al, 2011 ; Tsung & Gao, 2012 ; Tsung & Lau, 2019 ). Bhowmik and Kennedy ( 2017 ) found that it has been “common to attribute school failure for ethnic minority students in Hong Kong to problems with Chinese language education” (p. 69).…”
Section: Introductionmentioning
confidence: 99%
“…These students attend local kindergartens and primary/secondary schools but mostly take Chinese as a second language. Consequently, their reading proficiency significantly lags behind their Chinese counterparts for about 3–4 years, which largely undermines their confidence in Chinese language learning and in turn hinders their academic achievements, social integration and upward social mobility ( Leong et al, 2011 ; Loh and Tam, 2016 ). To address the pressing need, teachers and researchers have been seeking effective and tailor-made approaches derived from empirical evidence about CSL students’ characteristics in learning Chinese ( Gong et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%